2007
DOI: 10.1080/10410230701453884
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Smoking Media Campaign Messages: Theory and Practice

Abstract: This study examined televised anti-smoking advertisements that were designed to discourage adult and teen smoking. A content analysis of 399 television advertisements catalogued in the Media Campaign Resource Center (MCRC) database were evaluated to determine (a) whether the advertising content reflected core health communication theories used in the design of health campaign messages to change behavior and (b) the affective presentation of tobacco-control advertisements aimed to decrease smoking. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 37 publications
0
73
1
1
Order By: Relevance
“…transferring knowledge on the consequences of a behavior-could positively influence attitudes (cf. Cohen et al 2007). On the other hand, several researchers hsave suggested that explicitly modeling knowledge may increase predictive power of TPB.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…transferring knowledge on the consequences of a behavior-could positively influence attitudes (cf. Cohen et al 2007). On the other hand, several researchers hsave suggested that explicitly modeling knowledge may increase predictive power of TPB.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Hence, active university smokers would respond to a combination of rational (image and in-depth knowledge) and emotional (loved ones mourning) appeals in public service advertising in Australia [13]. Researchers also recommended integrating different calls for devising effective antismoking messages rather than relying on a single appeal in reducing smoking prevalence [25].…”
Section: Emotional Appealmentioning
confidence: 99%
“…research indicates that no single call in antismoking campaign is likely to have universal resonance among youth [16]. Cohen, Shumate, and Gold (2007) also suggest combining different appeals for devising effective antismoking campaign rather than using a single approach [25]. Combining emotional and rational approach in advertising can prove to be an effective strategy for antismoking campaigners.…”
Section: Introductionmentioning
confidence: 99%
“…Au sein des différentes actions de protection de la santé publique, la lutte au tabagisme serait l'enjeu bénéiciant des plus importants investissements publicitaires (Cohen, Shumate et Gold, 2007). L'eficacité de campagnes anti-tabagiques est admise (Lalonde et Heneman, 2004), malgré certaines réserves portant sur la méthodologie des études publiées (Brinn et al, 2010).…”
Section: La Campagne éTudiée Prémisses Théoriques D'une Campagne De Punclassified